An integrative rights-based approach to human development in Africa - Dejo Olowu (Pretoria University Law Press (PULP), 2009)
An integrative rights-based approach to human development in Africa by Dejo Olowu 2009 ISBN: 978-0-9814124-6-7 Pages: x 322 Print version: Available Electronic version: Free PDF available